L’appropriation négociée de l’espace public par les balayeuses de Casablanca - Leila Bouasria (Genre, Sexualité et Société)
The present article makes an attempt to bring into light the manners with which street sweepers in Casablanca negotiate their presence in public space. Their presence in this space makes apparent their dual belonging to minority categories, positioned at the intersection of gender and class hierarchies. The intersectional and interactionist approaches adopted in the analysis highlight forms of negotiated spatial appropriation through which a certain subjectivity emerges. In other words, the focus is less on documenting stigma and more on showing how certain attributes linked to gender or class also function as flexible resources. Through their tactics, the sweepers thus create a new frame of reference that reflects various logics. These are described in this article through a repertoire of values and a register of actions that reveal the paradoxical ambiguity of their presence in the streets of Casablanca. Furthermore, this negotiated appropriation of space can only emerge through lived experiences shaped by the emotions that the sweepers encounter as both agents and subjects. These appropriation dynamics operate on both semantic and emotional levels (the feelings associated with them). Indeed, acts of appropriation carry various meanings, shaped by the contexts in which they occur and the nature of the social ties involved.